Thalidomide and discoid lupus erythematosus: case series and review of literature - Giovanna Malara; Chiara Verduci; Maria Altomonte; Maria Cuzzola; Caterina Trifirò; Cristina Politi; Giovanni Tripepi (BioExcel Publishing Ltd, 2022)
Background: The anti-inflammatory drug, thalidomide, is often administered off-label especially in dermatology patients with diseases refractory to different medications. The drug's mechanism of action is not well understood but clinical evidence suggests an immunomodulatory function. Although this drug is a useful tool for several dermatoses, there are associations between its use and neurotoxic and teratogenic side effects. Consequently, it is reserved only for severe and refractory cases. Methods: Herein, we present a review about thalidomide focusing on its application in dermatology, particularly on discoid lupus erythematosus (DLE) treatment. We analyzed four cases of people who had a regression of DLE with a dosage of 50 mg thalidomide. Patients were followed to determine the conditions treated with thalidomide, dosage, efficacy, duration of treatment, side effects, adverse events and follow-up. A low dose of 50 mg/day induced a notable and rapid improvement within 1-2 months of treatment and no side effects have been reported so far. Results: We report four cases of DLE treated previously with the most common immunomodulatory agents with no results and finally successfully treated with thalidomide. In all four patients, despite a low dose of 50 mg/day, a notable and rapid improvement was obtained within a few months of treatment with no side effects. Conclusions: Notwithstanding the small cohort size, our experience confirms the efficacy of thalidomide for the treatment of DLE.